General chemistry : principles and modern applications / Ralph H Petrucci,...[et al.] - Petrucci, Ralph H.Author
This book is recognized for its superior problems, lucid writing, precision of argument, and precise and detailed treatment of chemistry. Its innovative pedagogical features, which encourage students to understand, apply, and synthesize content, reinforce the principles of general chemistry and provide the ideal platform for later studies. The new tenth edition boasts a number of improvements: including expanded coverage of organic chemistry, as well as a consistent 3-part structure (Analyze--Solve--Assess) for every worked example. All of the student-favourite, pedagogically rich elements of this textbook have returned in the tenth edition with renewed focus, including 10 to 25 new questions per chapter and updated integrative examples that all follow the Practice Example A and Practice Example B format